A COMPARATIVE ANALYSIS: THE SOCIAL WRONGS REVEALED & THE IDEOLOGIES BROUGHT IN EDITORIAL NEWS EXPOSING THE NEW KPK LAW - Christina Atika Yulina; Patricia Natasya Rhea Sudarna; Widi Handayani (Universitas Bunda Mulia, 2021)
This research is a comparative analysis between two mass media in producing politic news responding to the establishment of the new KPK law by using Critical Discourse Analysis. The research aims to look for and to compare the social wrongs and ideologies brought by the writers from the chosen texts. In order to do critical analysis discourse, the researchers use Fairclough analytic-three-dimensional framework which is wrapped in the four stages of Roy Bhaskar explanatory critiques presented by Fairclough (2013).The first stage focuses on the social wrong which has semiotic aspects that is analyzed through its linguistic choice by using Appraisal theory proposed by Martin and White. The social wrong of the text is represented by the use of attitude consisting of affect, appreciation, and judgment as it shows the writers’ attitude towards the related parties in the texts. The second stage identifies the obstacles to it being tackled through the analysis of the network of practices, the relationship of the semiosis to other elements and the semiosis itself. It is analyzed using Gee’s Seven Building Tasks of Language. It aims to analyze the areas of “reality” that are built through the texts, which can be used to understand the meaning of the discourse. It may also be used to understand different aspects of the meaning being created through discourse. The ideology of the text is represented by the significances, activities, identities, relationships, politics, connections, and sign systems & knowledge in the texts. The third stage considers whether the social order needs the problems/the social wrong. The last stage reveals the possible ways to tackle the obstacles. The findings from these steps of analysis are combined and interpreted together. It is found that the article produced by The Jakarta Post, as a verified news editorial by the Indonesian Press Council, apparently seems to share more negative attitudes compared to Independent Observer which is not verified yet. This shows the social wrong establishes in the social order: the politicization of the media, which is clearly unnecessary in the social order since it makes the media are politically polarized. Despite the ideological differences in the two articles, both articles basically share the same ideology: the importance of eradicating corruption in Indonesia.